Detailed Functional and Structural Phenotype of Bietti Crystalline Dystrophy Associated with Mutations in CYP4V2 Complicated by Choroidal Neovascularization - Fuerst, Nicole M. (Ophthalmic Genet, 2016)
PURPOSE: To describe in detail the phenotype of a patient with Bietti crystalline dystrophy (BCD) complicated by choroidal neovascularization (CNV) and the response to intravitreal Bevacizumab (Avastin ®; Genentech/Roche). METHODS: A 34-year-old woman with BCD and mutations in CYP4V2 (c.802-8_806del13/p.H331P:c992A>C) underwent a complete ophthalmic examination, full-field flash electroretinography (ERG), kinetic and two-color dark-adapted perimetry, and dark-adaptometry. Imaging was performed with spectral domain optical coherence tomography (SD-OCT), near infrared (NIR) and short wavelength (SW) fundus autofluorescence (FAF), and fluorescein angiography (FA). RESULTS: Best-corrected visual acuity (BCVA) was 20/20 and 20/60 for the right and left eye, respectively. There were corneal paralimbal crystal-like deposits. Kinetic fields were normal in peripheral extent. Retinal crystals were most obvious on NIR-reflectance and corresponded with hyperreflectivities within the RPE on SD-OCT. There was parafoveal/perifoveal hypofluorescence on SW-FAF and NIR-FAF. Rod > cone sensitivity loss surrounded fixation and extended to ~10° of eccentricity corresponding to regions of photoreceptor outer segment-retinal pigmented epithelium (RPE) interdigitation abnormalities. The outer nuclear layer was normal in thickness. Recovery of sensitivity following a ~76% rhodopsin bleach was normal. ERGs were normal. A subretinal hemorrhage in the left eye co-localized with elevation of the RPE on SD-OCT and leakage on FA, suggestive of CNV. Three monthly intravitreal injections of Bevacizumab led to restoration of BCVA to baseline (20/25). CONCLUSION: Crystals in BCD were predominantly located within the RPE. Photoreceptor outer segment and apical RPE abnormalities underlie the relatively extensive retinal dysfunction observed in relatively early-stage BCD. Intravitreal Bevacizumab was effective in treating CNV in this setting.